Development and Application of qPCR and RPA Genus- and Species-Specific Detection of Phytophthora sojae and P. sansomeana Root Rot Pathogens of Soybean - Rojas, J Alejandro (Plant disease, 2017)
Phytophthora root rot of soybean, caused by Phytophthora sojae, is one of the most important diseases in the Midwestern United States, and is estimated to cause losses of up to 1.2 million metric tons per year. Disease may also be caused by P. sansomeana; however, the prevalence and damage caused by this species is not well known, partly due to limitations of current diagnostic tools. Efficient, accurate, and sensitive detection of pathogens is crucial for management. Thus, multiplex qPCR and isothermal RPA (recombinase polymerase amplification) assays were developed using a hierarchical approach to detect these Phytophthora spp. The assays consist of a genus-specific probe and two species-specific probes that target the atp9-nad9 region of the mitochondrial genome that is highly specific for the genus Phytophthora. The qPCR approach multiplexes the three probes and a plant internal control. The RPA assays run each probe independently with a plant internal control multiplexed in one amplification, obtaining a result in as little as 20 mins. The multicopy mitochondrial genome provides sensitivity with sufficient variability to discern among different Phytophthora spp. The assays were highly specific when tested against a panel of 100 Phytophthora taxa and range of Pythium spp. The consistent detection level of the assay was 100 fg for the qPCR assay and 10 pg for the RPA assay. The assays were validated on symptomatic plants collected from Michigan (U.S.) and Ontario (Canada) during the 2013 field season, showing correlation with isolation. In 2014, the assays were validated with samples from nine soybean producing states in the U.S. The assays are valuable diagnostic tools for detection of Phytophthora spp. affecting soybean